Revolution, revival, and religious conflict in Sandinista Nicaragua - Smith, Calvin L. (Religion in the Americas, 2007)
This interdisciplinary study breaks new ground by exploring relations between Protestants (mainly Pentecostals) and the Sandinistas in revolutionary Nicaragua, which to date have received scant attention. It challenges the view that most Protestants supported the Sandinistas (in fact, the majority vigorously opposed them) and establishes why many believed Nicaragua was heading towards communism or totalitarianism. Meanwhile, the Sandinistas expressed irritation with Pentecostalism's otherworldliness and support for Israel. Pentecostals were harassed, even brutally repressed in the northern highlands, leading many to join the Contras. That a minority of Protestants supported the Sandinistas caused further problems. Pentecostals and Sandinistas were ideological rivals offering an alternative vision to the poor: revolution or revival. As Pentecostalism exploded, a collision between the two was inevitable.